Differential game in closed-loop supply chain of innovative products with double regrets of consumers - Qing Ma; Yao Peng; Zhenwei Liu (PLoS ONE, 2026)
In this paper, we consider a three-level dynamic closed-loop supply chain differential game model led by manufacturers and recycled by third-party recyclers in order to study the impact on the dynamic closed-loop supply chain of innovative products based on simultaneous occurrence of consumer purchase regret and replacement regret. Then, we obtain the optimal path for wholesale price, retail price and return effort by solving the differential game model. Specifically, we explore the influence of the coupling effect of consumer purchase regret and replacement regret on the supply chain through theoretical analysis and numerical simulation. The results show that consumer purchase regret leads to lower sales in the supply chain, which in turn causes a decrease in long-term profits of manufacturers and retailers, while consumer replacement regret will attract more consumers to increase sales, thereby increasing the long-term profits for manufacturers and retailers accordingly. However, consumer purchase regret does not affect the profit of recyclers. In addition, both types of consumer post-purchase regret prolong the product length of time in the market, and consumer replacement regret has a more significant effect on the length of time of product in the market. Meanwhile, lower consumer purchase regret and higher replacement regret can improve the performance of all members of the entire dynamic supply chain. However, these factors do not influence the recyclers.